A clustering based routing algorithm in IoT aware Wireless Mesh Networks. (July 2018) - Li, Jilong; Silva, Bhagya Nathali; Diyan, Muhammad; Cao, Zhenbo; Han, Kijun
Highlights: Our system achieve optimal network throughput. In IoT over WMN environment, a Load Balancing and Interference Delay Aware routing algorithm is used to avoid network traffic jam. The proposed scheme efficiently utilizes the available mesh station queue information and the number of mesh nodes that suffers from channel interference in the available path. This increases the network energy efficiency by managing the interference delay. Abstract: The Internet of Things (IoT) notion enables embedded devices to connect and share data through IP or the web. Interference routing metric and adaptive load balancing have gained much attention as the key challenges to overcome in IoT based wireless mesh networks (WMN) with the increase in wireless service performance. Moreover, IoT over WMN severely affected by network traffic caused by enormous data generation by a large number of users. Hence, we have proposed a clustering based routing algorithm considering an interference and load balancing routing metric that focuses on minimizing the existing issues of networks. In this study, we propose a scheme that reduces the end-to-end delay but also gives full consideration to both the quality on the entire route to the destination and to the expected lifetime of nodes with bottlenecks from heaped traffic in IoT. Simultaneously, it utilizes mesh station channel interference and queue information appropriately to address the identified challenges. The simulations results show that the proposed scheme performed superior to the existing routing metrics present in the current literature for similar purposes.